EXAMINING DESIGN AS STRATEGY DISCOURSE – Part 2 - Katoppo, Martin Luqman (School of Design Universitas Pelita Harapan, 2024)
I will review and examine each case study from the 7 papers in this JSDIS Vol. 6 Edition 1, to build a discourse on Design as Strategy. The framework for reviewing and examining each case study is to use 3 perspectives from the Design as Strategy point of view (Katoppo, 2024) which is also the sub-themes of the National Seminar on Social Design (SNDS) and the International Conference on Social Design (ICSD) 2024 (https://snds.uph.edu/), which are: 1. Body of Knowledge: The discourse start from the point of its definition to its extent in the design field, namely system design (i.e.: visual communication design), interaction design (i.e.: product design), and spatial design (i.e.: interior design and architecture) (Grimsgaard, 2023). 2. Innovation: In this discourse, it would investigate the causal relationship between Design as Strategy and Innovation. It will discuss how Design as Strategy becomes the driver of innovation in design practice, design pedagogy, and technology driven design (Bethune, 2022). In the context of technology driven design there are at least 3 innovation categories: the classic technology-driven innovation (Ottinger, 2021), the user- and design-driven innovation (Szymariska, 2017; Duczek, 2021), dan future artificial-driven innovation (Gartner, 2021; Beale, 2022). 3. Contribution to Social Change: The last discourse would build around the action, where Design as Strategy is implemented to make social change. It will discuss the impact for society, for the environment and for prosperity (Amatullo, et.al (ed.), 2021).